Identifying sources of resistance to late blight and black scurf, and other economically useful traits among interspecific potato hybrids - Z. Z. Evdokimova; M. V. Kalashnik (Труды по прикладной ботанике, генетике и селекции)
Background. This publication presents the results of a four-year (2016–2019) study undertaken to assess potato hybrids from the nurseries of preliminary tests and the nursery of the second tuber generation for their resistance to Phytophthora infestans (Mont.) de Bary and Rhizoctonia solani J.G. Kühn in the environments of Leningrad Province. Potato forms with a set of economically useful traits were identified as promising source material for further breeding.Materials and methods. The study covered the interspecific hybrids developed on the basis of the following species: Solanum vernei Bitt. et Wittm., S. megistacrolobum Bitt., S. chacoense Bitt., S. demissum Lindl., S. verrucosum Schelechtd., S. stoloniferum Schlechtd., S. polytrichon Rydb., S. andigenum Yuz. et Buk., S. rybinii Yuz. et Buk., and S. tuberosum Lindl. Late blight and black scurf resistance tests were performed using the methods approved for the potato selection technology.Results and conclusions. The possibility to select potato genotypes with high and medium resistance of their tops and tubers was ascertained under severe natural infection with P. infestans and R. solani. In the preliminary test nursery, from 4.0 to 62.0% of the tested accessions demonstrated high plant top resistance to late blight, and from 21.6 to 58.0% possessed tuber resistance. The analysis of resistance to black scurf showed that the average score for several years in the preliminary test nursery ranged from 6.3 to 7.6 points (the scale from 9 down to 1), while the percentage of highly resistant accessions was in the range of 25.9–70.7%. In the nursery of the second tuber generation, the average resistance across the years of study varied from 6.3 to 7.8 points, with the percentage of highly resistant hybrids ranging from 27.0 to 87.1%. The selected hybrids were distinguished by their increased productivity (31.4–42.9 t/ha), high marketability of tubers (89–98%), and dry matter content (16.6–19.5%). Source material with a set of economically useful features promising for breeding was identified.